APLIKASI GEOSPASIAL ANALISIS UNTUK PENENTUAN ZONA IMBUHAN AIRTANAH DI CAT WONOSOBO, PROVINSI JAWA TENGAH - Thomas Triadi Putranto; Wahju Krishna Hidajat; Annita Kusuma Wardhani (Diponegoro University, 2017)
Groundwater is the valuable resources for supplying daily necessity of human’s life that is going to increase in line with the increasing number of population. Therefore, groundwater needs to be well managed. Groundwater management can be done thoroughly within a groundwater basin for defining groundwater recharge zone. The groundwater recharge zone was conducted by applying geospatial analysis using weighted and scoring approach. This method was accomplished by overlaying the score of some parameters (hydraulic conductivity, precipitation, soil cover, slope, and groundwater depth of water table) using ArcGIS 10.3 software. The parameters were permeability of rocks, rainfall, soil type, slope and depth of superficial groundwater level. The result of geospatial analysis can be divided into two zones which are groundwater recharge zone and groundwater discharge zone.